2019
DOI: 10.1016/j.brainres.2017.12.037
|View full text |Cite
|
Sign up to set email alerts
|

Out of thin air: Hyperventilation-triggered seizures

Abstract: Voluntary hyperventilation triggers seizures in the vast majority of people with absence epilepsy. The mechanisms that underlie this phenomenon remain unknown. Herein, we review observations - many made long ago - that provide insight into the relationship between breathing and absence seizures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 119 publications
(177 reference statements)
1
19
1
Order By: Relevance
“…Our cases, as well as those previously reported ( Barker et al, 2012 ), confirm that in some individuals HV can cause HIHARSAA and suggest that alkalosis is the core of HIHARSAA-associated biochemical mechanism ( Schuchmann et al, 2009 , Lu et al, 2012 , Yang et al, 2014 , Salvati and Beenhakker, 2019 ).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our cases, as well as those previously reported ( Barker et al, 2012 ), confirm that in some individuals HV can cause HIHARSAA and suggest that alkalosis is the core of HIHARSAA-associated biochemical mechanism ( Schuchmann et al, 2009 , Lu et al, 2012 , Yang et al, 2014 , Salvati and Beenhakker, 2019 ).…”
Section: Discussionsupporting
confidence: 91%
“…Although the role of HV in typical AS activation has not been clarified ( Bomben et al, 2016 ), experimentally HV-induced alkalosis has been demonstrated to be a trigger of typical AS ( Schuchmann et al, 2009 , Lu et al, 2012 , Salvati and Beenhakker, 2019 ) and humans ( Yang et al, 2014 ). In murine models, alkalosis resulted in up-regulation of VGCCs, N-methyl-D-aspartate (NMDA)-type glutamate receptors as well as α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid (AMPA) receptors in cortical pyramidal neurons ( Schuchmann et al, 2009 , Lu et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…During hypoxia, K + channels are inhibited, leading to cellular depolarization and the release of neurotransmitters, resulting in hyperventilatory activity [22]. Hyperventilation (rapid breathing) is an acute way the body increases oxygen supply to tissues [86]. The precise mechanism through which the carotid body senses low oxygen and activates a response is still unfolding [22], however, RET generated ROS is involved [22,23].…”
Section: Ret Generated Ros In Physiologymentioning
confidence: 99%
“…HV is a major provocation technique used to trigger the typical 3-Hz spike-and-wave discharge (SWD) which is characteristic for absence epilepsy as more than 90% of patients who have absence epilepsy show SWD during HV. The non-specific thalamic projection system (NSTPS) which is a part of the thalamocortical networks triggered by respiratory alkalosis and considered to be the major induction of SWD associated with absence epilepsy during the process of HV [23]. HV is an efficient and safe activation method for epilepsy and seizure disorder provocation however there are certain contraindication to perform HV during EEG study which includes patients with cardiopulmonary disease, sickle cell anemia, Moy-Moya disease, subarachnoid and intracerebral bleeding and severe carotid stenosis [22].…”
Section: Technical Aspects Of Electroencephalographymentioning
confidence: 99%